Coping With Children Bullying Reflected In Charles Dickens' Oliver Twist(1838): An Individual Psychological Approach - Wardhana, Bayu, Dr. M. Thoyibi. M.S (2017)
The objectives of the study are: 1) to analyze characteristics of children bullying in Charles Dickens' Oliver Twist; 2) to analyze children bullying depicted by Charles Dickens's Oliver Twist; and 3) analyze how Oliver Twist coped with bullying. The type of the study used by the researcher is descriptive qualitative research. In this research, the researcher applies Psychological approach mainly Individual Psychology Theory of Alfred Adler. Individual Psychology Theory of Alfred Adler is used as a means to analyse the novel, in order to find out the main characters' why and how becoming bullying victim and its influence on his life, and how he coped with bullying . The results of the research show that there are 4 (four) characteristics of children bullying in Charles Dickens' Oliver Twist, namely an imbalance of power between the agressor and the victim, repeatedly incidence and duration, intentionality and proactive character of the aggression, and the intent to do harm.Children bullying depicted by Charles Dickens' Oliver Twist comes in term of physical bullying, verbal bullying, and social bullying. Oliver Twist coped with bullying was analyzed through six basic principles of individual psychology, those are inferiority feeling, striving for superiority, style of life, social interest, creative power and fictional finalism